(untitled) (International Journal of Nursing Education, 2022)
Abstract: Childhood Behaviour Disorder Autism is a fast growing problem worldwide according to present scenario. 1 in 100 children in India are suffering from childhood behaviour disorder Autism. This disorder has a drastic negative impact on the normal development of a child. Mothers are the primary care giver for their children. So that a strong knowledge and attitude of mothers child with Autism is the vital factor in proper guidance for behaviour management of their under developed child. Aim: The present pilot study was carried out with the aim of assessment of knowledge and attitude regarding childhood behaviour disorder Autism among mothers child with Autism. Material and method: 50 mothers child with Autism were selected for present experimental pilot study. Purposive sampling technique, structured teaching programme, semi structured questionnaire based on knowledge and attitude were implemented. The present pilot study was carried out 6.1.2022 to 13.1.2022 in the District Disability Rehabilitation Centre of Agartala. Result: pre-test knowledge of mothers about child hood behaviour disorder mean was 5.05, post-test knowledge of mothers about child hood behaviour disorder mean was 11.75 with standard deviation 2.195,t test value 18.160 and p value .000.So the result of pilot study of knowledge among mothers is significant. Pre-test positive (favourable) Attitude response mean was 10.7255, post test positive Attitude response was 13.2745, Standard deviation of pre-test positive response 1.73296, t test value 50, df 50 and p value .000, so favourable attitude response is significant. Conclusion: Mothers with lower in education, non-availability of child development centres facility and financial support, lack of awareness regarding Autism negatively impacted the study result which significantly improved in the end result of this experimental comparative study. Proper health education for improvement of knowledge and attitude is an important key factor for mothers how they should treat and care their child. According to the study education of mothers, financial support, healthcare support are the most important factors which can improve the knowledge and attitude of mothers.